Modeling of Electric and Magnetic Fields Around 132 kV Transmission Line - Kulkarni, G. A.; Gandhare, W. Z. (Acta Technica Jaurinensis, 2014)
Exposure to natural and manmade extremely low frequency (ELF) electromagnetic fields (EMF) have been a concern during previous years. Schumann Resonance (SR) phenomenon is the source of natural ELF EMFs. High voltage (HV) Transmission Lines is one of the major sources of manmade ELF EMFs. Staying around or close to transmission lines have reported to cause ill effects on human health. The health effects can be analyzed by measuring the external and internal fields. The main objective of this study is to do exposure assessment around HVAC line and model the same using a program developed in MATLAB.  A double circuit 132 kV, 50 Hz transmission line was selected for this purpose.ELF EMFs around HV line were measured using a low frequency analyzer ME 3830B. Measured external field levels were modeled using regression analysis, support vector machine (SVM), Neural Network (NN) and Hybrid technique. Finally comparative analysis of all modeling techniques was presented.